Obligatory private health insurance – a comparison of systems on the example of the solutions applied in Australia; the Netherlands and Switzerland - Ostrowska-Dankiewicz, Anna (Obligatoryjne prywatne ubezpieczenia zdrowotne – porównanie systemów na przykładzie rozwiązań stosowanych w Australii, Holandii i Szwajcarii, 2017)
The article deals with the functioning of systems characterized by the compulsory possession of private health insurance. It provides a general overview of how health insurance operates in selected countries, i.e. Australia, the Netherlands and Switzerland. The attention has been paid to active participation in the promotion of compulsory private health insurance and the taking of specific actions aimed at strengthening their participation. It has been indicated that subsidies and obligatory purchase are the most effective tools for promoting them alongside supporting mechanisms such as the offering of standardized products by insurers, co-financing and the imposition of penalties as a fiscal mechanism. The paper presents the features of the systems, the possibilities of their financing through the use of state subsidies and the amount of expenditures for involuntary participation in the health insurance system in relation to GDP in the analyzed countries
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 79-91
Keywords: health insurance system; private health insurance; system ubezpieczeń zdrowotnych; prywatne ubezpieczenia zdrowotne